Correlation between nosocomial pneumonia and ventilated patients in pediatric intensive care unit - Cahya Dewi; Purnomo Suryantoro; Roni Naning (Indonesian Pediatric Society Publishing House, 2016)
Background NP (NP) especially YAP (ventilator-associated pneu- monia) is the most common infection in intensive care unit, which correlates with the increasing of morbidity and mortality. There are some risk factors for development ofNP, the most important one is duration of mechanical ventilator and reintubation. Objective To determine the correlation between NP and use of mechanical ventilator in pediatric intensive care unit (PICU). Methods A matched case control study was conducted at Dr. Sardjito Hospital on all patients admitted to the PICU from 2004 until 2006. Case group was defined as all patients who had NP; age and sex matched control group included all patients not diagnosed as NP. Statistical analysis was done by using chi-square and t-tests as appropriate. Logistic regression analysis was done to determine the role of risk factors. Results One-hundred and forty-one patients were included in this study. The incidence of NP was 25. 7%. There was associa- tion between using mechanical ventilator (OR 1.08; 95%CI 1.07; 8.20, P=0.036) and duration of using mechanical ventilator more than four days (OR 1.75, 95%CI 1.87;18.02) with development of NP. There was a significant difference in event free survival of NP between those using mechanical ventilator group and those not using mechanical ventilator group (P<O.OOl). Conclusion There is an association between the use of mechani- cal ventilator and duration of use of mechanical ventilator more than four days with the development of NP